IMPLEMENTASI SPANNING TREE PROTOCOL (STP) PADA PERANCANGAN VIRTUAL LOCAL AREA NETWORK (VLAN) PADA PT. REGALINDO SAKTI JAKARTA - Vergina Maria Josefina Renwarin; Ummu Radiyah (Sekolah Tinggi Teknologi Informasi NIIT, 2021)
Information technology is growing rapidly and has become a necessity for every company. PT. Regalindo Sakti is a large company engaged in textile trading. Based on direct observations to the company, the business of PT. Regalindo Sakti is wide and shipment s of the textile industry can reach overseas. Large business fields require good network management to support communication and transactions with clients. The use of computer networks in this company does not yet have good network management, including the absence of redundancy or alternative routes that can handle data packets when a loop occurs and experiences a down on the network system. On the other hand, computer networks in several divisions have not provided access rights or privacy. This condition can be resolved by trying to implement network management with the Spanning Tree Protocol (STP) on the switch in order to provide redundant paths and prevent loops on the network and develop the network into a virtual local area network (VLAN). The results of the study by implementing STP can reduce network looping on the switch, namely by configuring the port with root status, which means the best path to go. The concept of spanning tree protocol provides a backup path in a topology that has the pot ential to have a redundant path, while the VLAN concept can divide network groups so that the network can be better managed and prevent the spread of viruses and worms